Bipolar II disorder in patients with a current diagnosis of recurrent depression. (1st March 2014) - Mosolov, Sergey; Ushkalova, Anna; Kostukova, Elena; Shafarenko, Alexey; Alfimov, Pavel; Kostyukova, Anastasiya; Angst, Jules
<x xml:space="preserve">Abstract</x> Objectives The prevalence of bipolar II disorder (BD‐II) in Russia has never been studied. Therefore, we sought to identify patients meeting diagnostic criteria for BD‐II among patients with a current diagnosis of recurrent depressive disorder (RDD) through the use of the Russian versions of the Hypomania Checklist (HCL‐32) and Bipolarity Index scales for differentiating between BD‐II and RDD. Methods In a non‐interventional diagnostic study, we selected 409 patients aged between 18 and 65 years from two medical settings with (i) a current diagnosis of RDD, (ii) an illness duration of at least three years, and (iii) at least two affective episodes. The diagnosis was based on clinical assessment and confirmed by the Russian version of the Mini International Neuropsychiatric Interview. All patients were assessed by the HCL‐32, the Bipolarity Index, and the Personal and Social Performance Scale. Results Among patients with a current diagnosis of RDD, 40.8% had a diagnosis of bipolar disorder (bipolar I disorder: 4.9%; BD‐II: 35.9%). The average time lag from onset to a correct diagnosis of BD‐II was 15 years and patients were treated only with antidepressants. The sensitivity of the Russian version of the HCL‐32 at the optimal cutoff point (≥14.0) was 83.7%, and its specificity was 71.9%. The Bipolarity Index showed significant differences between the total scores of the patients with BD‐II and RDD (31.8 versus 20.2; p < 0.0001). The optimal threshold was ≥22.0 (sensitivity 73.5%; specificity 72.3%). Conclusions In Russia, diagnostic errors are an important cause of the non‐detection of bipolar disorder, particularly BD‐II. The Russian version of the HCL‐32 and the Bipolarity Index, as additional tools, could be useful for bipolarity screening.